(untitled) (Pedagogy of Higher and Secondary Education, 2001)
In clause, the contents of concept of “readiness ” to various kinds of activity and in particular to creative activity are considered (examined). The specific features of concept “readiness ” of creative activity with reference to process of musical training come to light. The structural components of readiness to creative activity of the pupils are defined(determined). The generated attributes of readiness under influence of the model, developed by us are stated.